MEMAHAMI DINAMIKA AGRESIVITAS PAJAK: PERAN LIKUIDITAS, LEVERAGE, DAN CSR DALAM KONTEKS PERUSAHAAN MANUFAKTUR BEI - Junaidar Handayanto, Adrian; Sularsih, Hermi; Himawan Wibisono, Sukarno; Fitria Hayuningtyas, Ruri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Tax aggressiveness is a specific activity that includes transactions, where the main objective is to reduce the company's tax liability. The purpose of this study was to determine the application of liquidity, leverage and corporate social responsibility to tax aggressiveness. Research conducted using quantitative methods. The type of data used in this study is secondary data from manufacturing companies on the Indonesia Stock Exchange 2018-2022. The data collection techniques used by researchers are literature study documentation and documentation methods. The data analysis technique in this study uses descriptive analysis test, classical assumption test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis. The results of the study of liquidity have a positive and significant effect, Leverage has no positive and significant effect Corporate social responsibility has no positive and significant effect on industrial sector manufacturing companies located on the IDX 2018-2022 period.